Developing Computer Assisted Media of Pneumatic System Learning Oriented to Industrial Demands - Wahyu Dwi Kurniawan; Agung Prijo Budijono; Nur Aini Susanti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
This study aimed to develop learning media of pneumatic systems based on computer-assisted learning as an effort to improve the competence of students at the Department of Mechanical Engineering, Faculty of Engineering UNESA. The development method referred to the 4D model design of Thiagarajan comprising the steps of: define, design, develop, and desseminate. The results showed that the expert validation average score included in both categories was 3.54, indicating the learning application acceptable. A limited test showed effective results, namely: (a) Analysis of the data included in the category of learning was good (3.64), indicated by students’ enthusiasm in the learning process; (b) Teaching learning activities were categorized as good, the students actively involved in learning, and the most dominant activity was doing tasks while discussing; (c) Learning objectives were both achieved individually and classically; (d) The students showed a positive response expressed by the students’ interest, excitement, and motivation to follow the learning process.